Impacto da pandemia da COVID-19 no rastreamento, diagnóstico e tratamento do câncer de mama em mulheres a partir de 50 anos, no estado do Pará - DIAS, Paula Danniele dos Santos (Universidade Federal do Pará, 2024)
Breast cancer is the second most common in the world and the most common among women. Early diagnosis and treatment estimate a good prognosis for the disease. After the pandemic was declared by the World Health Organization (WHO), States had to adopt restrictive measures to contain the spread of the disease. Brazil was one of the four countries with the highest number of confirmed Covid-19 infections, with high transmissibility rates causing a collapse in health services. As a result, the maintenance and regular treatment of several diseases, including breast cancer, were affected. Objective: to analyze whether the Covid-19 pandemic affected the screening, diagnosis and treatment of breast cancer, in women aged 50 and over, in the State of Pará. Method: The study was retrospective, cross-sectional, with a quantitative approach, using secondary data obtained from the Information Technology Department of the Unified Health System (DATASUS). An analysis was carried out of the number of exams carried out in the post-pandemic (2018-2019) and pandemic (2020-2021) period based on the percentage variation, and application of the chi-square test and G test for the time taken to perform exams and time to start treatment. Results: During the pandemic period, a greater number of screening mammograms (+3.68%), cytological (+23.68%), histological (+10.7%) and a lower number of diagnostic mammograms (-38.7%) were observed %). The time interval for carrying out the exams was up to 30 days for screening and diagnostic exams during the pandemic period. The observed time to start treatment was greater than 60 days, with a greater number of cases treated during the pandemic period. Conclusion: the study points out that statistically the Covid-19 pandemic did not interfere with the screening, diagnosis and treatment of breast cancer, in women over 50 years old, in the State of Pará. The effects of Covid-19 will only possibly be observed at long-term, therefore, studies should be carried out that permeate the development of strategies that prepare health services for a future state of health emergency, to mitigate greater impacts on the health of the population.